O tronco nos espaços públicos de Dianópolis: o esquecimento dos sertanejos representados na obra de Bernardo Élis - Dias, Gleidson Soares (Universidade Federal do Tocantins, 2021)
The article deals with the power of the colonels, represented in O Tronco, by Bernardo Élis, a work set in theevents that took place in Vila do Duro, today Dianópolis, State of Goiás, which occurred between 1917 and 1918. The work demonstrates the oligarchic power, cruelty and coronelismo and jagunçagem in the north of Goiás at that time. It reveals the ills and tragedies of a society marked by inequality and manipulation. In a claiming manner, this work portrays the social reality of the backcountry Goiás and breaks down subhuman conditions, as in an appeal by the man of the backlands, forgotten by the governments and at the mercy of thepower and legitimate domination of their masters. Imbued with these issues, I decided to approach O trunk, with the main reason that this book contains a narrative that portrays the lives of many people in my homeland,the current Dianópolis - TO. I intend to offer a narrative that is not limited to the chronicle of events, reachingwhat we define today as a historical novel. I was born in Dianópolis and grew up listening to my grandparentstell this story of struggles and battles of men and women who were subjected to the degrading conditions of survival in Povoado do Duro. My intention is to indicate how the strength of coronelismo is manifested in thememories preserved in the public spaces of the city, a manifestation that puts the poor countrymen into oblivion.